Religion, Law, and State Power: The Dynamics of Legal Contestation in Indonesian Presidential Elections - Alfarisi, Muhammad Adib; Fatimah, Siti; Astuti, Eka Zuni Lusi (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2024)
This article examines the legal and political dynamics of the relationship between religion and the state in Indonesia, particularly in the context of presidential elections. Since the nation’s founding, this relationship has been a subject of contestation—beginning with the Jakarta Charter controversy and reemerging in the post-truth era through the rise of identity politics and populism. Employing library research and Michel Foucault’s heuristic framework, the study identifies three dominant paradigms in the religion–state relationship: secularist, traditionalist, and reformist or moderate Islamic. It argues that Indonesia’s current model aligns with the reformist Islamic paradigm, characterized by a reciprocal relationship in which the state supports the development of religion, while religion provides moral and ethical guidance to the state. The state integrates Islamic ethical values—such as honesty, justice, and brotherhood—into governance and social life, fostering a mutually beneficial framework. This symbiosis does not aim to establish a theocracy but rather promotes a morally grounded state apparatus. The study contributes to ongoing scholarly discussions by offering a framework for constructing a harmonious relationship between religion and the state in pluralistic societies. It concludes that strengthening reformist Islamic values can reinforce Indonesia’s democratic resilience and enhance the spiritual and ethical foundations of its political order. Artikel ini mengkaji dinamika hukum dan politik dalam hubungan antara agama dan negara di Indonesia, khususnya dalam konteks pemilihan presiden. Sejak awal berdirinya negara, hubungan ini telah menjadi subjek perdebatan—bermula dari kontroversi Piagam Jakarta dan kembali mencuat di era pasca-kebenaran melalui menguatnya politik identitas dan populisme. Dengan menggunakan metode studi pustaka dan pendekatan heuristik Michel Foucault, penelitian ini mengidentifikasi tiga paradigma dominan dalam relasi agama dan negara: sekularis, tradisionalis, dan Islam reformis atau moderat. Penelitian ini berargumen bahwa model hubungan yang berkembang di Indonesia saat ini selaras dengan paradigma Islam reformis, yang ditandai dengan hubungan timbal balik di mana negara mendukung perkembangan agama, sementara agama memberikan panduan moral dan etika bagi negara. Nilai-nilai etika Islam—seperti kejujuran, keadilan, dan persaudaraan—diintegrasikan ke dalam tata kelola pemerintahan dan kehidupan sosial, membentuk kerangka kerja yang saling menguntungkan. Simbiosis ini tidak bertujuan membentuk teokrasi, melainkan mendorong terbentuknya negara yang berlandaskan moral. Studi ini memberikan kontribusi terhadap diskursus ilmiah yang sedang berkembang dengan menawarkan kerangka untuk membangun hubungan yang harmonis antara agama dan negara dalam masyarakat pluralistik. Ditegaskan bahwa penguatan nilai-nilai Islam reformis dapat memperkokoh ketahanan demokrasi Indonesia serta memperdalam fondasi spiritual dan etika dalam tatanan politiknya.